THE RELATIONSHIP BETWEEN ISLAMIC FINTECH INNOVATION AND PUBLIC TRUST IN THE GLOBAL ERA - Triana Apriani; Wiwin Suhada; Ifah Masrifah (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The rapid development of financial technology has transformed the global financial industry, including the Islamic finance sector. Islamic fintech innovation has emerged as an alternative financial solution that integrates technological advancement with Sharia principles. This study aims to analyze the relationship between Islamic fintech innovation and public trust in the global era. Using a quantitative approach, data were collected through questionnaires distributed to users of Islamic fintech services. The study examines the influence of service innovation, perceived security, accessibility, transparency, and Sharia compliance on public trust. The results indicate that Islamic fintech innovation significantly affects public trust, particularly through transparency and security aspects. The findings suggest that Islamic fintech institutions must strengthen digital innovation while maintaining ethical and Sharia-based financial principles to enhance public confidence and long-term sustainability.